Pengaruh Motivasi, Kompensasi Kerja, dan Disiplin Kerja, terhadap Kinerja Karyawan: Studi PDAM Titra Moedal Kota Semarang - Fitriyantina, Sagita; Sudarsi, Sri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine the influence of motivation, work compensation, and work discipline on employee performance. This research was conducted at PDAM Tirta Moedal, Semarang City using employees as samples. In determining the sample, this study used the Slovin formula to determine the sample size. Test the validity of the data using factor analysis. Data analysis was carried out using SPSS version 23 software. The research results showed that motivation had a positive and significant influence on employee performance, work compensation also played a role in influencing employee performance, apart from that work discipline had a positive and significant influence on employee performance. This research makes contributions both theoretically and practically.